Down-regulation of the Notch Pathway in Human Airway Epithelium in Association with Smoking and Chronic Obstructive Pulmonary Disease - Tilley, Ann E; Harvey, Ben-Gary; Heguy, Adriana; Hackett, Neil R; Wang, Rui; O'Connor, Timothy P; Crystal, Ronald G (American journal of respiratory and critical care medicine, 2009)
The airway epithelium of smokers is subject to a variety of mechanisms of injury with consequent modulation of epithelial regeneration and disordered differentiation. Several signaling pathways, including the Notch pathway, control epithelial differentiation in lung morphogenesis, but little is known about the role of these pathways in adults. We tested the hypotheses that Notch-related genes are expressed in the normal nonsmoker small airway epithelium of human adults, and that Notch-related gene expression is down-regulated in healthy smokers and smokers with chronic obstructive pulmonary disease (COPD). We used microarray technology to evaluate the expression of 55 Notch-related genes in the small airway epithelium of nonsmokers. We used TaqMan quantitative polymerase chain reaction (PCR) to confirm the expression of key genes and we used immunohistochemistry to assess the expression of Notch-related proteins in the airway epithelium. Changes in expression of Notch genes in healthy smokers and smokers with COPD compared with nonsmokers were evaluated by PCR. Microarray analysis demonstrated that 45 of 55 Notch-related genes are expressed in the small airway epithelium of adults. TaqMan PCR confirmed the expression of key genes with highest expression of the ligand DLL1, the receptor NOTCH2, and the downstream effector HES1. Immunohistochemistry demonstrated the expression of Jag1, Notch2, Hes1, and Hes5 in airway epithelium. Several Notch ligands, receptors, and downstream effector genes were down-regulated in smokers, with more genes down-regulated in smokers with COPD than in healthy smokers. These observations are consistent with the hypothesis that the Notch pathway likely plays a role in the human adult airway epithelium, with down-regulation of Notch pathway gene expression in association with smoking and COPD.